Avadhī kī rāshṭrīya kavitāem - Miśra, Śyāmasundara (Sāhitya Niketana, 1993)
Selected poems by 19th and 20th century Awadhi authors on the Indian freedom struggle during the British rule and the theme of nationalism, published on the golden jubilee of the August revolution; includes short introduction of the poets.
"Agasta-krānti kī svarṇa jayantī ke avasara para"--Half t.p.
In Awadhi; preface in Hindi.
Selected poems by 19th and 20th century Awadhi authors on the Indian freedom struggle during the British rule and the theme of nationalism, published on the golden jubilee of the August revolution; includes short introduction of the poets.
Keywords: Nationalism / India / Poetry. / http://id.loc.gov/authorities/subjects/sh2010103304; Awadhi poetry / 20th century.; Awadhi poetry / 19th century.; India / Politics and government / 1919-1947 / Poetry.